Adaptation of the Systematic Review Framework to the Assessment of Toxicological Test Methods: Challenges and Lessons Learned With the Zebrafish Embryotoxicity Test - AKGÜN ÖLMEZ, SEVCAN GÜL (OXFORD UNIV PRESS, 2019)
Systematic review methodology is a means of addressing specific questions through structured, consistent, and transparent examinations of the relevant scientific evidence. Thismethodology has been used to advantage in clinical medicine, and is being adapted for use in other disciplines. Although some applications to toxicology have been explored, especially for hazard identification, the present preparatory study is, to our knowledge, the first attempt to adapt it to the assessment of toxicological test methods. As our test case, we chose the zebrafish embryotoxicity test (ZET) for developmental toxicity and its mammalian counterpart, the standard mammalian prenatal development toxicity study, focusing the review on how well the ZET predicts the presence or absence of chemical-induced prenatal developmental toxicity observed in mammalian studies. An interdisciplinary team prepared a systematic review protocol and adjusted it throughout this piloting phase, where needed. The final protocol was registered and will guide the main study (systematic review), which will execute the protocol to comprehensively answer the review question. The goal of this preparatory study was to translate systematic review methodology to the assessment of toxicological test method performance. Consequently, it focused on the methodological issues encountered, whereas the main study will report substantive findings. These relate to numerous systematic review steps, but primarily to searching and selecting the evidence. Applying the lessons learned to these challenges can improve not only our main study, but may also be helpful to others seeking to use systematic review methodology to compare toxicological test methods. We conclude with a series of recommendations that, if adopted, would help improve the quality of the published literature, and make conducting systematic reviews of toxicological studies faster and easier over time.
Keywords: systematic review; test method comparison; zebrafish embryotoxicity test; prenatal developmental toxicity; malformations; ENVIRONMENTAL-HEALTH SCIENCE; EVIDENCE-BASED MEDICINE; DEVELOPMENTAL TOXICOLOGY; REPORTING QUALITY; THALIDOMIDE; TOXICITY; VALIDATION; HARMONIZATION; METAANALYSIS; TERMINOLOGY